2021
DOI: 10.1021/acs.orglett.1c02764
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage C–H Acylation of Tyrosine-Containing Oligopeptides with Alcohols

Abstract: The selective tagging of amino acids within a peptide framework while using atom-economical C–H counterparts poses an unmet challenge within peptide chemistry. Herein, we report a novel Pd-catalyzed late-stage C–H acylation of a collection of Tyr-containing peptides with alcohols. This water-compatible labeling technique is distinguished by its reliable scalability and features the use of ethanol as a renewable feedstock for the assembly of a variety of peptidomimetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…To evaluate the feasibility of our oxygenation manifold, we first selected the fully protected tyrosine derivative 1 a housing a removable 2‐pyridyloxy group as DG [12b–c,e,14] . After evaluation of the reaction conditions, [15] we observed that the desired acetoxylation event could occur to provide mixtures of mono‐ and diacetoxylated compounds 2 a and 2 a’ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the feasibility of our oxygenation manifold, we first selected the fully protected tyrosine derivative 1 a housing a removable 2‐pyridyloxy group as DG [12b–c,e,14] . After evaluation of the reaction conditions, [15] we observed that the desired acetoxylation event could occur to provide mixtures of mono‐ and diacetoxylated compounds 2 a and 2 a’ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Following this work, the same group, in 2021, reported a similar Pd-catalyzed C–H acylation of Tyr-bearing peptides utilizing simple primary alcohols 84 as aldehyde precursors, having applications toward biologically relevant peptides (e.g., 85a ) (Scheme 21b ). 60b Both these acylation reactions were proposed to proceed via the TBHP-enabled in situ generation of acyl radical intermediates (see Scheme 38 ).…”
Section: Tyrosine Modificationsmentioning
confidence: 99%
“…Some of the well-known reactions performed on the phenolic moiety of tyrosine included cyclization via oxidative dearomatization, Pictet-Spengler cyclization or halogenation/alkylation via classical electrophilic aromatic substitution reactions. Organometallic element mediated modern organic reactions like C (sp 2 )À H [3] and OÀ H functionalizations along with etherification, [4] borylation, [5] acetoxylation, [6] halogenation, [7] arylation, [8] acylation reaction, [9] on the phenolic moiety of tyrosine are open the door towards the vast area in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%